Investigating the impact of e-banking, employee job security, innovativeness, and productivity on organizational performance: Perspectives from South Africa - Dalia Ayme Opoko Apendi; Kaodui Li; Jean Baptiste Bernard Pea-Assounga; Prince Dorian Rivel Bambi (Sustainable Futures)
The necessity of this study arises from the increasing adoption of e-banking and its potential impact on organizational performance, particularly in developing economies like South Africa. While technological innovation has been widely linked to improved business efficiency, most research has focused on developed countries, overlooking the unique challenges and opportunities faced by emerging markets. In South Africa, the banking sector plays a crucial role in economic growth, yet the effects of e-banking on organizational performance remain underexplored. Additionally, recent studies have connected technological innovation to organizational performance, predominantly in developed countries, neglecting the potential impacts of employee productivity (EP), employee job security (EJS), and employee job stress (EJST). This study examines how EP, EJS, and employee innovativeness (EIN) mediate, and employee job stress (EJST) moderates, the relationship between e-banking (EB) and organizational performance (OP) in South African banks. Using a quantitative approach, data were collected from 378 respondents, and analyzed through structural equation modeling via SmartPLS. Findings reveal positive associations between EB, OP, EP, EJS, and EIN. Additionally, EP, EJS, and EIN partially mediate the EB-OP relationship, while EJST negatively moderates it. The study underscores the importance of EB for organizational growth but suggests exploring alternative strategies for boosting performance. Despite its contributions, the study is limited by its focus on a single industry and geographic region. Future research should explore broader contexts and alternative performance-enhancing strategies. This research contributes comprehensively to the literature on financial technology and organizational performance in economically developing nations, offering insights for scholars and policymakers.